Effect of ECAP on copper electrode in spark machining. (2020) - Gopal, R.; Thirunavukkarasu, K.
Abstract: This paper analyses the behavior of spark erosion machining in terms of output performance such as rate of machining, rate of tool erosion and surface roughness corresponding to the input parameters effect on discharge current, spark existing time and spark absence time with respect to. The experimentation was conducted based on Box-Behnken design using bare electrode and a ECAP processed electrode. The regression models were developed and optimized with Response Surface Methodology. From the analysis, it was concluded that the spark erosion machining quality is significantly high with equal channel angular pressed copper electrode.